Verbal Prompting To Improve Everyday Cognition in MCI and Unimpaired Older Adults - Thomas, Kelsey R. (2013)
OBJECTIVE: This study investigated the effect of verbal prompting on elders’ 10-year longitudinal change in everyday cognition. Differential effects of prompting associated with impaired cognitive status were also examined. METHOD: At baseline, 2,802 participants (mean age=73.6 years, mean education=13.5 years) from the ACTIVE clinical trial were classified as unimpaired, having amnestic mild cognitive impairment (MCI) or non-amnestic MCI based on psychometric algorithm. Participants were given the Observed Tasks of Daily Living (OTDL; a behavioral measure with tasks involving medication management/finances/telephone use) at baseline and at 1-, 2-, 3-, 5-, and 10-year follow-ups. When participants said “I don’t know” or did not respond to an item, they received a standardized verbal prompt. At each occasion, Unprompted (sum of items correct without prompting) and Prompted (sum of items correct including both prompted and unprompted) scores were derived for each participant. Multi-level modeling, adjusting for demographics/health/training group, was used to determine the trajectories of OTDL performance. RESULTS: In general, persons with MCI performed at lower levels than those who were unimpaired (amnestic<non-amnestic<unimpaired), and for all groups, prompted performance exceeded unprompted in all years. There was differential performance of the prompting conditions over time; prompted performance, unlike unprompted, was relatively protected from age-related decline, and persons with MCI experienced greater improvement due to prompting. CONCLUSION: Very simple prompting appears to enhance and maintain performance on a task of everyday cognition over 10 years for both unimpaired and mildly-impaired older adults.